THE EFFECT OF RECIPROCAL TEACHING WITH SELF CORRECTION ON THE 8th GRADE STUDENTS’ READING COMPETENCY AT SMPN 6 DENPASAR - ., GUSTI AYU PUTU OLIARNI; ., Prof. Dr. Dewa Komang Tantra, M.Sc., Ph.; ., Dra. Luh Putu Artini, MA., Ph.D. (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2014)
This study aimed at investigating whether there is a significant difference in reading competency between a) the students, b) good readers, c) poor readers who are treated by using reciprocal teaching with self correction and those who are treated by using reciprocal teaching with teacher?s correction. This study was an experimental study recruiting 104 students as the sample of the research. Post-test only comparison group design was applied as the research design. The data obtained from the post test were analyzed by using descriptive and inferential statistic analysis. Through the descriptive analysis, it was found that the mean score of the group who were taught by using reciprocal teaching with self correction was higher than those who were taught by using reciprocal teaching with teacher?s correction. It means that the students who were treated by using reciprocal teaching with self correction is better than those who were taught by using reciprocal teaching with teacher?s correction, good readers who were thought by using reciprocal teaching with self correction is better than those who were taught by using reciprocal teaching with teacher?s correction, poor readers who were treated by using reciprocal teaching with self correction is also better than who were taught by using reciprocal teaching self correction. These findings provide empirical evidence of the importance to consider strategy and types of correction in teaching reading.keyword : Reading competency, Reciprocal teaching, Self correction